2019
DOI: 10.2478/bog-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood adaptation and life satisfaction among land-lost farmers: Critiquing China’s urbanisation-driven land appropriation

Abstract: Large-scale rural land appropriation and displacement, driven by the unprecedented urban growth currently experienced in China, has created millions of land-lost peasants who live in the city but remain culturally, socially and institutionally rural. The situation has attracted growing attention in the literature because of its negative social impact, but relatively few studies have addressed how land-lost farmers adapt to urban ways of life and what factors influence their life satisfaction. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Second, the multifaceted impact of land consolidation on the resettlers and how this is linked to satisfaction demands more attention [35]. Our results show that land consolidation created significant changes in villagers' livelihood, income, and living environment.…”
Section: Discussionmentioning
confidence: 81%
“…Second, the multifaceted impact of land consolidation on the resettlers and how this is linked to satisfaction demands more attention [35]. Our results show that land consolidation created significant changes in villagers' livelihood, income, and living environment.…”
Section: Discussionmentioning
confidence: 81%
“…This literature implies that the resettlement process can have a range of long‐run negative consequences for communities and that compensation programs often do not adequately compensate resettled populations for everything they have lost (Cernea 1997; Vanclay 2017). A loss of well‐being (e.g., life satisfaction, self‐rated health, or mental health) seems to be common (Hwang et al 2007; Tong, Zhu, and Lo 2019; Xi and Hwang 2011). However, Randell (2016) finds that a generous compensation program led to more positive outcomes for the case of one rural resettled population in Belo Monte.…”
Section: Discussionmentioning
confidence: 99%
“…A related study found similar impacts on depressive symptoms using multiple waves of data (Xi and Hwang 2011). Displaced Chinese farmers report lower life satisfaction, due largely to disrupted agrarian livelihoods (Tong, Zhu, and Lo 2019). A notable exception is described in Randell (2016), who finds that one compensated population in the Belo Monte dam region reported increased subjective well‐being, at least in the short run, in part because their household wealth improved via compensation.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few researches have focused on this, there is an urgent need to evaluate migrants’ life satisfaction under urbanisation and examine its influence factors [ 25 , 26 ]. This study aimed to fill this gap by conducting a survey towards migrants in 18 communities across two major cities of Yangtza Delta in China, seeking to address the central research questions: 1) whether migrants are satisfied with life following urbanisation; 2) which key factors have significantly affected their life satisfaction; 3) how to increase levels of life satisfaction among rural-to-urban migrants.…”
Section: Introductionmentioning
confidence: 99%